ANALISIS PENETAPAN NOMOR 253/PDT.P/2023/PN BPP TENTANG PERUBAHAN ANGGARAN DASAR PADA PERSEKUTUAN KOMANDITER (CV): Analysis of Determination Number 253/Pdt.P/2023/PN Bpp concerning Articles of Association Amendment on Limited Partnership (CV) - Bintani, Putri Shilah (Jurnal Globalisasi Hukum., 2024)
The Decision of the Bpp District Court Number 253/Pdt.P/2023/PN Bpp provides a decision regarding heirs who can replace a deceased active partner in a Limited Partnership (CV). This examination will discuss whether there are other aspects that need to be considered by the judge in making the decision. Generally, the court will consider both juridical and non-juridical aspects. This research uses a qualitative method, producing descriptive analysis, and the data collection used is through literature review to obtain primary legal materials and secondary legal materials. The result of this research, the analysis of decision number 253/Pdt.P/2023/PN Bpp shows that the judge issued a decision that should have been declaratory in nature, but in this case, the judge issued a condemnatory decision and included a constitutive clause.